m6A RNA modification in tumor-associated macrophages: emerging roles in cancer immunity - Chen, Xi; Pu, Shanrui; Lian, Kun; Li, Lihua; Jiang, Xiulin (Frontiers in Immunology, 2025)
N6-methyladenosine (m6A) is the most prevalent internal modification of eukaryotic mRNA and has emerged as a pivotal regulator of gene expression at the post-transcriptional level. In the tumor immune microenvironment, tumor-associated macrophages (TAMs) represent a highly plastic and heterogeneous population that profoundly influences cancer progression, immune evasion, and therapeutic response. Recent studies have uncovered that m6A modification, mediated by dynamic “writers,” “erasers,” and “readers,” exerts critical regulatory effects on TAM differentiation, polarization, and functional reprogramming. By modulating the stability, translation, and decay of transcripts involved in inflammatory signaling, metabolic adaptation, and immune checkpoints, m6A shapes the balance between tumor-promoting (M2-like) and tumor-suppressive (M1-like) macrophage phenotypes. Moreover, dysregulation of m6A machinery in TAMs has been linked to the suppression of anti-tumor immunity and resistance to immunotherapy, highlighting its translational potential as a therapeutic target. This review summarizes current advances in understanding the roles and mechanisms of m6A modification in TAM biology, discusses its implications in tumor immunity, and outlines the challenges and opportunities of targeting the m6A–TAM axis for cancer treatment.